Evaluation of long-term phosphorus fertilizer placement, rate, and source, and research in the U.S. Midwest - Edwards, Cristie LeAnne (Kansas State University, 2017)
The appropriate management for phosphorus (P) fertilizer can have significant agronomic, economic, as well as environmental impact. Studies in Kansas have evaluated different management systems to determine best management practices (BMP). The first component of this dissertation is a comprehensive review of tillage system and P fertilizer placement interaction. This review included studies completed in the U.S. Midwest. Results of this review showed greater corn yields with conventional tillage and broadcast applications when soil test P levels (STP) were below 20 mg P kg⁻¹. However, soybean yield was highest in no-till systems with broadcast P fertilizer applications. The second component if this dissertation was a long-term study conducted in Kansas to evaluate the effect of P fertilizer placement on corn and soybean production. Results showed that under strip-tillage, P fertilizer placement significantly affected corn growth, but, seldom resulted in yield response difference among placement methods. Phosphorus application as starter fertilizer at planting showed the most consistent yield response. In addition to the agronomic aspect of this study, the third component of this dissertation consisted of an economic analysis using partial budgets calculated using both fixed and varying prices and costs to compare management practices. With decreased application costs associated with deep banding in strip-tillage system, net returns are greater than broadcast applications. The highest net responses were observed with starter P fertilizer applications. The fourth component of this dissertation included a study evaluating the effects of chelated fertilizer on nutrients, such as P, Fe, Mn, and Zn in soybean. Results from our study showed that both ethylenediamine tetraacetic acid (EDTA)+P and hydroxyethyl ethylenediamine tetraacetic acid (HEDTA)+P resulted in greater concentrations and uptake of Fe and lower Mn uptake in soybean. However, the application of glucoheptonate (GCH)+P had no negative effect on Mn uptake compared to EDTA+P and HEDTA+P. Across locations, EDTA+P and HEDTA+P showed higher yield than GCH+P. The use of long-term studies and comprehensive reviews can provide a unique perspective and better understanding of the most appropriate BMPs for P fertilizer management. Many agronomic and environmental implications of P fertilizer management and the interactions with tillage systems and soils may only become noticeable after multiple years or in a variety of conditions.
Keywords: Placement; Strip-tillage; Chelated micronutrientsPhosphorus Fertilizer